Validation of a laser device for assessing high-speed running in an outdoor team sport setting - Duthie, G. M.; Robertson, S.; Ball, K.; Haycraft, J.; Bright, L.; Parkinson, T.; Billingham, J.; Aughey, R. J. (Sports Engineering, 2025)
Laser-based systems are commonly used to measure running speed in many sports. The resulting output can be used to assess performance, profile athletes and measure the effect of coaching interventions. This study aimed to compare the running speed output from a commercially available laser (Laser Speed, MuscleLAB) with a three-dimensional motion capture system (Vicon, Oxford Metrics Group), a commonly recognized "gold standard" method of measuring human movement. Conducted on a professional football stadium pitch during daylight, 29 participants completed between one and six straight line, high-speed runs (> 6.9 m·s-1) over a distance of about 20 m. Instantaneous velocity was obtained from each system and compared across a total of 25,082 samples. Results showed high agreement between the two systems, with a mean root mean square error of 0.06 m·s-1 recorded and an association between the systems of r = 0.99. When considered across the 29 participants, minor differences were noted, with a mean error of 0.03 m·s-1. Higher error tended to be observed as running speed increased, with low variation in results across different participants. Laser-based speed assessment technology presents as an easy to use, relatively low-cost option for the assessment of linear running speed in outdoor team sport settings.